A series of Cu(II) based di-hydrazide complexes obtained through solvent exchange: Their efficient dye degradation and magnetic study. (1st October 2019) - Adhikary, Amit; Samanta, Debabrata
Graphical abstract: A series of copper-dihydrazide complexes were synthesized where a structural transformation was observed upon solvent exchange. A change in the magnetic interaction was revealed after the transformation. Also, one complex shows efficient dye degradation behaviour. Abstract: The Cu(II) complex [Cu2 (L)(H2 O)2 (MeOH)2 ](NO3 )2 (1 ) was synthesized, where H2 L = N, N′bis(2-hydroxy-3-methoxybenzyledene)succinohydrazide. Upon dissolving single crystals of1 in H2 O, the two coordinated MeOH molecules were replaced by two H2 O molecules around the coordination sphere of the Cu(II) ion, resulting in the formation of [Cu2 (L)(H2 O)4 ](NO3 )2 (2 ). Further, to see the effect, if any, of the anion in the molecular assembly process, [Cu2 (L)(H2 O)2 (MeOH)2 ]·(2MeOH)·(ClO4 )2 (3 ) was synthesized. Complex3 also displayed a phase transformation to [Cu2 (L)(H2 O)4 ]·(ClO4 )2 (4 ) by a solvent exchange process. However, interestingly, the reaction of H2 L with Cu(BF4 )2 in MeOH resulted in [Cu2 (L)(H2 O)4 ]·(4H2 O)·(SiF6 ) (5 ). No MeOH was coordinated in this case and5 did not show any transformation. The mechanistic pathway of the transformation, from DFT calculations, shows a stepwise exchange of MeOH by H2 O and supports the transformation from a thermodynamic point of view. Single crystal X-ray crystallography reveals that the flexible H2 L ligand is stretched to its maximum length and almost linear structures were obtained for all the complexes. Further complex1 shows efficient dye degradation with Rhodamine B, Congo red as well as methylene blue, where Congo red and Rhodamine B dye can be easily separated as precipitates from solution. UV–Vis and photoluminescence studies confirm the dye degradation process. The structural transformation also brings about a change in the intermolecular magnetic exchange. Magnetic studies of complex1 reveal antiferromagnetic interactions through intermolecular hydrogen bonding interactions and a coupling constant ( J ) of −1.6 cm −1 was obtained from the fitting. However, for complex2, the coupling constant ( J ) was changed to −2.1 cm −1 .